EFEKTIVITAS KEBERHASILAN PEREKAMAN HARIMAU SUMATERA (Panthera tigris sumatrae Pocock,1929) MENGGUNAKAN KAMERA JEBAKAN DI SPTN I SIPURAK HOOK TAMAN NASIONAL KERINCI SEBLAT: Effectiveness of the Success of Sumatran Tiger Recording (Panthera tigris sumatrae Pocock, 1929) Using Camera Trap at SPTN I Sipurak Hook Kerinci Seblat National Park - Asrizal Paiman; Cory Wulan; Fredy Almi Saputra (Fakultas Kehutanan Universitas Jambi, 2021)
This research aims to evaluate the results of trials of the effectiveness of the use of camera traps in knowing the problems and constraints that can be used in developing strategies and solutions to the problem of using camera traps for Sumatran tigers. Number of camera traps installed as many as 14 cameras. Installation of camera traps is distinguished by three mounting heights of soil that is 35 cm, 40 cm, 45 cm. Data analysis is done to collect data recording every camera trap with Sumatran tiger object. The results showed that there were 4 trap camera units that successfully recorded the Sumatran tiger, with the most effective recording activity of Sumatran tiger is at 45 cm height with 86%. There are 4 trap camera units that suffered damage and loss. The most effective mounting height in the recording process is the height of the 45 cm installation with 60% comparison.